Full-focal graphite negative electrode material, preparation method, application and lithium ion battery

CN122822755BActive Publication Date: 2026-10-30CENT SOUTH UNIV +4
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202611278379.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-21
Publication Date
2026-10-30
Estimated Expiration
2046-08-21

AI Technical Summary

Technical Problem

人造石墨负极作为锂离子电池的核心关键材料,目前面临资源供给紧张、生产能耗高、碳排放量大等多重难题

Benefits of technology

[0048]1)实现石油焦的全利用,即100%的石油焦均用作石墨负极材料;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122822755B_ABST
    Figure CN122822755B_ABST
Patent Text Reader

Abstract

The present application belongs to the field of lithium ion battery negative electrode materials, and particularly relates to full-coke-based graphite negative electrode material, a preparation method, application and lithium ion battery thereof. The preparation method of the full-coke-based graphite negative electrode material innovatively granulates green coke tail powder and coke powder respectively, and couples sintering of coke F1 from the green coke tail powder and coke F2 from the coke powder according to the outer cavity and the inner cavity respectively, and further controls the starting loading mode and the like in combination, so as to realize cooperation, realize full quantization graphitization of coke raw materials, and obtain materials with different application requirements such as long cycle and fast charging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lithium-ion battery anode materials, specifically relating to all-coke-based graphite anode materials, their preparation methods, applications, and the field of lithium-ion batteries. Background Technology

[0002] With the rapid development of the global new energy vehicle and electrochemical energy storage industries, the demand for lithium-ion batteries has experienced explosive growth. As a core material for lithium-ion batteries, artificial graphite anodes currently face multiple challenges, including tight resource supply, high production energy consumption, and large carbon emissions. On the one hand, the main raw material for artificial graphite production is high-quality petroleum coke. Due to upgrades in domestic refining processes, petroleum coke production capacity is gradually decreasing, leading to a widening market supply gap. On the other hand, the crushing process of artificial graphite coke generates a large amount of raw coke tailings, which current technologies cannot efficiently and effectively utilize, resulting in a serious waste of high-quality carbon resources and creating environmental pressure.

[0003] Specifically, the production process suffers from two main resource losses: First, the coke raw material crushing process generates approximately 30% raw coke tail powder with a particle size between 0 and 6 μm. This powder has excessively fine particle size, large specific surface area, low tap density, and poor particle morphology, making it difficult to directly reuse in the preparation of artificial graphite anodes. Currently, it is mostly disposed of as fuel or aluminum electrolysis anode raw material for low-value processing. Second, the graphitization process of anode materials requires crystal structure transformation to be completed at a high temperature of 2300-3000℃, resulting in high energy consumption and carbon emissions. In the traditional Acheson furnace graphitization process, approximately 80 GJ of energy is consumed to produce 1 ton of anode material, corresponding to carbon emissions of 8.7 tons of CO2 equivalent; at the same time, the heat utilization rate of the traditional Acheson furnace is less than 40%, resulting in significant energy waste.

[0004] To address the problems existing in the prior art, some improvement solutions have also been disclosed. For example, patent document CN105990581A discloses a method for preparing composite graphite anode materials. This method involves mixing petroleum coke, spherical or flake graphite, and a binder, then placing the mixture in a stirring / rolling granulation device, heating it while stirring / rolling, and then graphitizing the resulting material. After graphitization, the material is sieved to remove large particles, and the undersize material is the composite graphite anode material. Another example is patent document CN109748274A, which discloses a low-cost method for preparing composite particulate graphite anode materials. This method involves mixing coke material and asphalt powder at a mass ratio of 100:1 to 100:20 to obtain a mixture; placing the mixture in a graphitization furnace for graphitization treatment to obtain composite particulate graphitized material; classifying the composite particulate graphitized material to obtain graded material; and sieving and demagnetizing the graded material to obtain the composite particulate graphite anode material.

[0005] In summary, although existing technologies have reported many improved graphitization schemes, current methods still struggle to achieve full recycling of coke. Summary of the Invention

[0006] To address the shortcomings of existing technologies, a method for preparing a fully coke-based graphite anode material is provided, aiming to achieve full graphitization utilization of coke and prepare a graphite material with comprehensive high performance.

[0007] The second objective of this invention is to provide the all-coke-based graphite anode material prepared by the aforementioned method and its applications.

[0008] A third objective of this invention is to provide a lithium-ion battery comprising the aforementioned coke-based graphite anode material.

[0009] Raw coke tail powder (also referred to as tail powder) has excessively fine particles, a large specific surface area, low tap density, and poor morphology, making graphitization difficult and costly, and thus unsuitable for reuse in the production of artificial graphite anodes. Traditional anode preparation methods can only utilize semi-finished coke powder; furthermore, the graphitization process for producing artificial graphite is characterized by low thermal efficiency, high energy consumption, and high carbon emissions. To address these technical problems, this invention provides the following technical solution:

[0010] A method for preparing a coke-based graphite anode material, comprising the following steps:

[0011] Step 1:

[0012] The coke raw material is crushed and collected to obtain raw coke tail powder and coke powder; then they are granulated separately to obtain coke F1 and coke F2.

[0013] Step 2:

[0014] Coke F1 and coke F2 are continuously graphitized in a vertical continuous graphitization furnace;

[0015] The vertical continuous graphitization furnace includes the furnace body;

[0016] The furnace body consists of two concentric cavities, an outer cavity and an inner cavity, and has a double-cavity coaxial sleeve structure. It is divided into a feeding zone, a preheating zone, a graphitization zone, a cooling zone and a discharging zone from top to bottom in the vertical direction.

[0017] Both the outer and inner cavities are equipped with material downward channels; the outer cavity has a coke F1 inlet in the feeding area and a GF1 outlet in the unloading area for extracting graphitized coke F1 products (also known as GF1).

[0018] The inner cavity has a coke F2 inlet in the feeding area and a GF2 outlet in the unloading area for extracting the graphitized product of coke F2 (also known as GF2).

[0019] The initial stage of continuous graphitization: coke F1 is filled into the feeding area of ​​the outer cavity, the preheating area of ​​the inner cavity, and the graphitization area of ​​the inner cavity; coke F2 is filled into the feeding area of ​​the inner cavity; after the initial loading, the graphitization area is first heated to the pretreatment temperature T1, and then the temperature is further increased to the graphitization temperature T2 for graphitization; the temperature T2 is 2500~3200℃; the holding time at temperature T2 is 2~6h;

[0020] Continuous graphitization stage: After the initial stage, the graphitized product of coke F1 is collected from the GF1 outlet, and coke F1 is continuously added in the feeding area of ​​the outer cavity. The coke F1 flows through the feeding area, preheating area, graphitization area and cooling area of ​​the outer cavity, and the graphitized product of coke F1 is collected from the GF1 outlet of the unloading area.

[0021] Furthermore, coke F2 is continuously added in the inner cavity feeding zone. The coke F2 flows through the inner cavity feeding zone, preheating zone, graphitization zone, and cooling zone, and the coke F2 graphitization product is collected from the GF2 outlet in the unloading zone.

[0022] The temperature of the material in the cooling zone is 80~200℃.

[0023] This invention innovatively granulates raw coke tail powder and coke powder separately according to the requirements, and couples the coke F1 from the raw coke tail powder and the coke F2 from the coke powder into the outer cavity and inner cavity respectively (coupled graphitization). In addition, it combines the joint control of the initial filling method, etc., to achieve synergy, which can realize the full graphitization of coke raw materials and obtain materials with various application requirements such as long cycle and fast charging.

[0024] In this invention, the coke raw material is petroleum coke;

[0025] In this invention, the raw coke tail powder and coke powder are classified by particle size. Coke powder refers to semi-finished particles that meet the particle size requirements obtained from crushing coke raw materials. Raw coke tail powder refers to waste material with a particle size smaller than coke powder.

[0026] For example, in this invention, coke raw materials are crushed and coke powder with a particle size of 6~15μm and raw coke tail powder (crushing byproduct) with a particle size of less than 6μm are collected.

[0027] The volatile matter content of raw coke tail powder and coke powder is 8-20%, and the true density is 1.3-1.5 g / cm³. 3 The sulfur content is 0.5%~4%.

[0028] In this invention, raw coke tail powder, polymer a, polymer b, and pore-forming agent are mixed and granulated to obtain coke F1;

[0029] Among them, the thermal decomposition temperature of polymer a is 900~1200℃; polymer b is a water-soluble polymer;

[0030] Coke powder and polymer b are mixed and granulated to obtain coke F2.

[0031] In this invention, polymer a includes at least one of high-temperature asphalt, high-temperature resin, and high-temperature building adhesive;

[0032] Polymer b includes at least one of sodium carboxymethyl cellulose, sodium carboxymethyl starch, starch, hydroxypropyl cellulose, polyacrylic acid, sodium polyacrylate, acrylic acid-acrylamide copolymer, and polyvinyl alcohol;

[0033] Pore-forming agents include at least one of silicon carbide, boron nitride, and nickel chloride;

[0034] The weight ratio of raw coke tail powder, polymer a, polymer b, and pore-forming agent is 1:0.01~0.05:0.01~0.05:0.001~0.01; it can further be 1:0.03~0.04:0.02~0.03:0.005~0.006.

[0035] The weight ratio of coke powder to polymer b is 1:0.01~0.05; it can be further 1:0.02~0.03.

[0036] In this invention, the temperature T1 is 600~1200℃; it can further be 800~1200℃.

[0037] In this invention, the heating rate V1 to temperature T1 is 2~10℃ / min, and can be further 5~10℃ / min;

[0038] The heat preservation time at temperature T1 can be 1~5h, and can be further extended to 2~3h.

[0039] Temperature T2 is 3000~3200℃.

[0040] The heating rate V2 to temperature T2 is 10~50℃ / min, and can be further 30~50℃ / min;

[0041] The heat preservation time at temperature T2 can be 4~5 hours.

[0042] The temperature of the material in the cooling zone is 80~150℃.

[0043] The preparation method described in this invention can use GF1 and GF2 as graphitized products separately, or they can be reasonably mixed and adjusted as needed to prepare graphite materials that take into account comprehensive performance.

[0044] The present invention also provides a coke-based graphite anode material prepared by the preparation method described above.

[0045] The present invention also provides an application of the all-coke-based graphite anode material prepared by the above preparation method, which is used to prepare lithium-ion batteries.

[0046] The present invention also provides a lithium-ion battery comprising a coke-based graphite anode material prepared by the preparation method described in the present invention.

[0047] Beneficial effects:

[0048] 1) Achieve full utilization of petroleum coke, that is, 100% of petroleum coke is used as graphite anode material;

[0049] 2) By independently granulating raw coke tail powder with polymer a, polymer b and pore-forming agent to obtain coke F1, and then co-calcining it with independently granulated coke F2, the graphitization process can be promoted, the permeability during the graphitization process can be improved and the removal of impurities can be promoted, thereby solving the problem that raw coke tail powder is difficult to graphitize and reuse in negative electrode materials.

[0050] 3) Couple the graphitization of specially granulated coke F1 and coke F2 to further optimize the loading method of the vertical continuous graphitization furnace, realize the graphitization transformation of the negative electrode material in the furnace, and avoid the mixing between different batches of negative electrode materials, thereby achieving low-cost and low-carbon emission graphite negative electrode material preparation.

[0051] 4) Coke F1 graphite products (GF1 extracted products such as GF1-330 type anode material) can meet the market demand for high-rate and high-power graphite anode materials; Coke F2 graphite products (GF2 extracted products such as GF2-350 type anode material) are long-cycle type and can meet the demand for long-cycle graphite anodes in the wind, solar and energy storage fields. Attached Figure Description

[0052] Figure 1 This is a schematic diagram of a vertical continuous graphitization furnace, where 1 is the outer cavity of the furnace body; 2 is the inner cavity of the furnace body; A is the feeding zone of the furnace body; B is the preheating zone of the furnace body; C is the graphitization zone of the furnace body; D is the cooling zone of the furnace body; E is the unloading zone of the furnace body; 1A is the feeding zone of the outer cavity; 1E is the unloading zone of the outer cavity; 2A is the feeding zone of the inner cavity; 2B is the preheating zone of the inner cavity; 2C is the graphitization zone of the inner cavity; 2D is the cooling zone of the inner cavity; 2E is the unloading zone of the inner cavity.

[0053] Figure 2 SEM image of the coke tail powder;

[0054] Figure 3 SEM image of coke powder;

[0055] Figure 4 The optical diagram for focal length F2;

[0056] Figure 5is the SEM image of the graphitized material GF1 prepared in Example 1;

[0057] Figure 6 is the SEM image of the graphitized material GF2 prepared in Example 1;

[0058] Figure 7 is the initial charge-discharge curve of the graphitized material GF1 prepared in Example 1;

[0059] Figure 8 is the initial charge-discharge curve of the graphitized material GF2 prepared in Example 1;

[0060] Figure 9 is the 0.5C cycle diagram of the graphitized material GF2 prepared in Example 1; DETAILED DESCRIPTION

[0061] In the present invention, graphitization is carried out using a vertical continuous graphitization furnace (also referred to as a dual-chamber furnace or vertical furnace) as shown Figure 1 , wherein the vertical continuous graphitization furnace comprises a furnace body and conventional supporting heating devices; the furnace body includes two sets of concentric chambers, namely an outer chamber 1 and an inner chamber 2, which has an inner and outer dual-chamber coaxial sleeve structure, and is divided into a feeding zone (as shown Figure 1 in zone A), a preheating zone (as shown Figure 1 in zone B), a graphitization zone (as shown Figure 1 in zone C), a cooling zone (as shown Figure 1 in zone D) and a discharging zone (as shown Figure 1 in zone E) sequentially from top to bottom along the vertical direction; that is, the same height regions of the outer chamber 1 and the inner chamber 2 are all provided with a feeding zone, a preheating zone, a graphitization zone, a cooling zone and a discharging zone;

[0062] Both the outer chamber 1 and the inner chamber 2 are provided with a material descending channel; wherein the feeding zone (1A) of the outer chamber 1 is provided with a coke F1 inlet, and the discharging zone (1E) is provided with a GF1 outlet for collecting the graphitized product of coke F1;

[0063] The inner chamber 2 is divided into a feeding zone (2A), a preheating zone (2B), a graphitization zone (2C), a cooling zone (2D) and a discharging zone (2E) from top to bottom; wherein the feeding zone (2A) of the inner chamber 2 is provided with a coke F2 inlet, and the discharging zone (2E) is provided with a GF2 outlet for collecting the graphitized product of coke F2;

[0064] In the present invention, the steps of performing graphitization using the furnace include, for example:

[0065] Step 1:

[0066] The coke raw material is pulverized and collected to obtain raw coke fine powder and coke powder; then granulation is performed respectively to prepare coke F1 and coke F2;

[0067] Step 2:

[0068] Coke F1 and coke F2 are continuously graphitized in a vertical continuous graphitization furnace;

[0069] The initial stage of continuous graphitization: the feeding area (1A) of the outer cavity 1 is first filled with coke F1; the feeding area (2A) of the inner cavity 2 is filled with coke F2, and the preheating area (2B) and graphitization area (2C) of the inner cavity 2 are filled with coke F1; after the initial loading, the temperature is first heated to the pretreatment temperature T1, and then the temperature is further increased to the graphitization temperature T2 to carry out graphitization;

[0070] Continuous graphitization stage: After the initial stage, the graphitized product of coke F1 is taken out from the GF1 outlet, and coke F1 is continuously added in the feeding area (1A) of the outer cavity 1. The coke F1 flows through the feeding area (1A), preheating area, graphitization area and cooling area of ​​the outer cavity 1, and the graphitized product of coke F1 (GF1) is taken out from the GF1 outlet of the unloading area (1E).

[0071] Furthermore, coke F2 is continuously added in the feeding zone (2A) of the inner cavity 2. The coke F2 flows through the feeding zone (2A), preheating zone (2B), graphitization zone (2C), and cooling zone (2D) of the inner cavity 2, and the coke F2 graphitization product (GF2) is extracted from the GF2 outlet of the unloading zone (2E).

[0072] This method can simultaneously prepare all-coke-based graphite anode materials containing graphitized F1 and / or F2 products.

[0073] In this invention, raw coke tail powder, high-temperature binder, aqueous polymer solution and pore-forming agent are mixed, stirred, briquetized, dried and calcined to obtain coke F1;

[0074] Coke powder and aqueous polymer solution are mixed, stirred, granulated, and dried to obtain coke F2;

[0075] Coke F1 is used to fill the feeding zone (1A) of the outer cavity 1 and the preheating zone (2B) and graphitization zone (2C) of the inner cavity 2 of the vertical continuous graphitization furnace.

[0076] The coke F2 is used to fill the feeding area (2A) of the inner cavity 2 of the vertical continuous graphitization furnace.

[0077] Subsequently, coke F1 and coke F2 are continuously fed from the hoppers of the feeding area (1A) of the outer cavity 1 and the feeding area (2A) of the inner cavity 2, respectively, with the feeding speed matching the unloading speed;

[0078] The vertical furnace is heated to T1 at a heating rate of V1 to remove volatiles, and then heated to T2 at a heating rate of V2 for graphitization. The material is held at T2 for t1. Then the material enters the cooling zone for water cooling. After the material temperature drops to T3, it is discharged from the discharge zone at a certain discharge rate.

[0079] After the temperature of the graphitization furnace stabilizes, coke F1 and coke F2 are continuously added in the feeding zone, and the graphitized products produced in the unloading zone are GF1 and GF2 respectively.

[0080] After being crushed, shaped, sieved, and demagnetized, GF1 is used to obtain the finished graphite anode material, which is GF1-330.

[0081] After depolymerization, sieving, and demagnetization, GF2 is used to obtain graphite anode material, namely GF2-350.

[0082] The aforementioned raw coke tailings are the tailings produced by crushing raw petroleum coke; the particle size is 0.1~6μm, the volatile matter is 8~20%, and the true density is 1.3~1.5g / cm³. 3 The sulfur content is 0.5%~4%;

[0083] Preferably, the particle size is 1~3μm, the volatile matter content is 10~20%, and the true density is 1.3~1.4g / cm³. 3 The sulfur content is 0.5%~2%;

[0084] The coke powder mentioned is a semi-finished product produced by grinding raw petroleum coke; its particle size is 6~15μm, volatile matter is 8~20%, and true density is 1.3~1.5g / cm³. 3 The sulfur content is 0.5%~4%;

[0085] Preferably, the particle size is 9-12 μm, the volatile matter content is 10-20%, and the true density is 1.3-1.4 g / cm³. 3 The sulfur content is 0.5%~2%;

[0086] High-temperature adhesives include at least one of high-temperature asphalt, high-temperature resin, and high-temperature construction adhesive;

[0087] The aqueous polymer in the aqueous polymer solution includes at least one of sodium carboxymethyl cellulose, sodium carboxymethyl starch, starch, hydroxypropyl cellulose, polyacrylic acid, sodium polyacrylate, acrylic acid-acrylamide copolymer, and polyvinyl alcohol.

[0088] Preferably, the concentration of the aqueous polymer in the aqueous polymer solution is 1% to 5%;

[0089] Preferably, the weight ratio of the raw coke tail powder, the high-temperature binder, the water-soluble polymer in the aqueous polymer solution, and the pore-forming agent is 1:0.01~0.05:0.01~0.05:0.001~0.01; more preferably, it can be 1:0.03~0.05:0.02~0.04:0.005~0.008.

[0090] Preferably, the weight ratio of coke powder to water-soluble polymer in the aqueous polymer solution is 1:0.01~0.05; more preferably, it can be 1:0.02~0.04.

[0091] The V1 is 2~10℃ / min, and the T1 temperature is 600~1200℃;

[0092] The V2 is 10~50℃ / min, the temperature of T2 is 2500~3200℃, and the heat preservation time t1 is 2~6h;

[0093] The temperature of T3 is 80~200℃;

[0094] In this invention, petroleum coke is mechanically pulverized to obtain coke powder (raw coke semi-finished product micro powder) with a particle size of 6~15μm and raw coke tail powder with a particle size of less than 6μm.

[0095] As an optional solution, in the following examples, the raw coke tailings are the tailings produced by crushing raw petroleum coke (SEM image shown). Figure 2 The particle size is 0.1~6μm, the volatile matter content is 8~20%, and the true density is 1.3~1.5g / cm³. 3 The sulfur content is 0.5%~4%; preferably, the particle size is 1~3μm, the volatile matter is 10~20%, and the true density is 1.3~1.4g / cm³. 3 The sulfur content is 0.5%~2%;

[0096] The coke powder (see SEM image) Figure 3 This is a semi-finished product produced from the pulverization of raw petroleum coke; its particle size is 6~15μm, volatile matter is 8~20%, and true density is 1.3~1.5g / cm³. 3 The sulfur content is 0.5%~4%; preferably, the particle size is 9~12μm, the volatile matter is 10~20%, and the true density is 1.3~1.4g / cm³. 3 The sulfur content is 0.5%~2%;

[0097] Example 1

[0098] Step 1:

[0099] (a): Preparation of F1 pyroxen

[0100] Raw coke tail powder, high-temperature binder, aqueous polymer solution and pore-forming agent are mixed, stirred, briquetteed, dried and calcined to obtain coke F1;

[0101] The high-temperature binder is high-temperature asphalt (a type of high-temperature petroleum asphalt with a softening point of 200℃).

[0102] The aqueous polymer solution is a 2% sodium carboxymethyl cellulose aqueous solution;

[0103] The pore-forming agent is silicon carbide;

[0104] The weight ratio of the raw coke tail powder, high-temperature binder, water-soluble polymer and pore-forming agent in the aqueous polymer solution is 1:0.04:0.03:0.006.

[0105] The calcination atmosphere was N2, the calcination temperature was 1200℃, and the time was 2 hours.

[0106] The particle size of coke F1 is 5mm.

[0107] (b): Preparation of F2 pyroxenon

[0108] Coke powder and an aqueous polymer solution (2% sodium carboxymethyl cellulose aqueous solution) were mixed, stirred, briquetteed, and dried to obtain coke F2 (see optical image). Figure 4 );

[0109] The weight ratio of coke powder to water-soluble polymer in the aqueous polymer solution is 1:0.03.

[0110] Step 2: Loading

[0111] Coke F1 is used to fill the feeding area (1A) of the outer cavity 1, the preheating area (2B) of the inner cavity 2, and the graphitization area (2C) of the inner cavity 2 of the vertical continuous graphitization furnace.

[0112] The coke F2 is used to fill the feeding area (2A) of the inner cavity 2 of the vertical continuous graphitization furnace.

[0113] Step 3: Graphitization

[0114] The vertical furnace is heated to T1 (800℃) at a heating rate of V1 (5℃ / min) and held for 2 hours. Then it is heated to T2 (3000℃) at a heating rate of V2 (30℃ / min) for graphitization treatment (4 hours). The material is then cooled in the cooling zone. After the material temperature drops to T3 (120℃), the graphitized products produced in the feeding zone are GF1 and GF2.

[0115] Step 4: Continuous graphitization

[0116] Coke F1 and coke F2 are continuously fed from the hoppers above the feeding area (1A) of the outer cavity 1 and the feeding area (2A) of the inner cavity 2, respectively, and continuous graphitization is achieved based on the graphite process in step 3, wherein the feeding speed is matched with the unloading speed.

[0117] After being crushed, shaped, sieved, and demagnetized, GF1 is used to obtain the finished graphite anode material, which is GF1-330.

[0118] After depolymerization, sieving, and demagnetization, GF2 is used to obtain the graphite anode material GF2-350.

[0119] Example 2

[0120] Compared to Example 1, the only difference is that the pelletizing conditions in step 1 were changed. The experimental groups were as follows:

[0121] Group A: Change the formulation components of step 1(a), that is, the high-temperature binder is phenolic resin; the aqueous polymer solution is 2% polyvinyl alcohol aqueous solution; and the pore-forming agent is nickel chloride.

[0122] Group B: In step 1(a), the weight ratio of raw coke tail powder, high-temperature binder, water-soluble polymer in water-based polymer solution, and pore-forming agent is 1:0.03:0.02:0.005.

[0123] In step 1(b), the weight ratio of coke powder to water-soluble polymer in the aqueous polymer solution is 1:0.02.

[0124] All other operations and parameters are the same as in Example 1.

[0125] Example 3

[0126] Compared with Example 1, the only difference is that the graphitization conditions in step 3 are changed, for example, T1, T2, etc.

[0127] Group A: Change the heating rate, that is, V1 is 10℃ / min; V2 is 50℃ / min;

[0128] Group B: Change the temperature, that is, T1 is 1200℃; T2 is 3200℃; T3 is 80℃;

[0129] Group C: Change the heat preservation time, that is, the heat preservation time at temperature T1 is 3 hours and the heat preservation time at temperature T2 is 5 hours.

[0130] Comparative Example 1

[0131] Compared with Example 1, the only difference is that in step 2, no coke F1 is added to the feeding area (1A) of the outer cavity 1. All other operations and parameters are the same as in Example 1.

[0132] Comparative Example 2

[0133] Compared with Example 1, the only difference is that in step 2, no coke F1 is added to the preheating zone (2B) and graphitization zone (2C) of the inner cavity 2 in the initial stage; all other operations and parameters are the same as in Example 1.

[0134] Comparative Example 3

[0135] Compared with Example 1, the only difference is that in step 1(a), the pore-forming agent is missing in the coke F1; all other operations and parameters are the same as in Example 1.

[0136] Comparative Example 4

[0137] Compared with Example 1, the only difference is that in step 1(a), the high-temperature binder is missing in the char F1. The missing high-temperature binder is supplemented by an equal weight of water-based polymer. All other operations and parameters are the same as in Example 1.

[0138] Comparative Example 5

[0139] Compared with Example 1, the only difference is that in step 3, the graphitization temperature T2 is 2200℃, and all other operations and parameters are the same as in Example 1.

[0140] Comparative Example 6

[0141] Compared with Example 1, the only difference is that in step 3, the heat preservation time under T2 is 1 hour, and all other operations and parameters are the same as in Example 1.

[0142] Comparative Example 7

[0143] Compared with Example 1, the only difference is that in step 3, the graphitization feeding temperature T3 is 600℃, and all other operations and parameters are the same as in Example 1.

[0144] The physicochemical properties of the waste coke modified graphite in Examples 1-3 and Comparative Examples 1-7 were tested respectively, and the test results are shown in Tables 1-3.

[0145] The testing method is as follows:

[0146] The working electrode was prepared according to the mass ratio of active material (negative electrode material generated in each case): conductive agent (Super P): sodium carboxymethyl cellulose (CMC): styrene-butadiene rubber (SBR) = 95:1.5:1.5:2. A lithium metal sheet was used as the counter electrode, a ceramic separator was selected, and the electrolyte was LB-5315C organic electrolyte produced by Guotai Huarong. 2016-type button batteries were assembled in an argon-filled glove box. The electrochemical performance of the assembled batteries was tested using a Blue Battery Testing System (CT3001A). The initial charge-discharge curve test was conducted at a rate of 0.1 C, with a voltage range of 0.001~1.5 V; the rate charge-discharge tests were conducted at rates of 0.1 C, 0.2 C, 0.5 C, 1 C, and 2 C, with a voltage range of 0.001~1.5 V; and the cycle test was conducted at a rate of 0.5 C, with a voltage range of 0.001~1.5 V.

[0147] The test results for GF1-330 are shown in Table 1, and the test results for GF2-350 are shown in Table 2.

[0148] The statistical results of process stability and continuous graphitization yield are shown in Table 3.

[0149] Table 1: GF1-330 test results for each case:

[0150] Table 2: GF2-350 Test Results:

[0151] Table 3: Statistical results of process stability and continuous graphitization yield for each case:

[0152] As shown in Tables 1 to 3, the innovative method of granulating raw coke tail powder and coke powder separately, combined with special granulation and loading method control, can achieve synergy, realize full utilization of coke, and obtain materials that meet the requirements of different applications such as long cycle and fast charging.

Claims

1. A method for preparing a coke-based graphite anode material, characterized in that the steps include... include: Step 1: The coke raw material is crushed and collected to obtain raw coke tail powder and coke powder; They were then granulated separately to obtain coke F1 and coke F2; The raw material for coking is petroleum coke; The coke raw material is crushed and collected to obtain coke powder with a particle size of 6~15μm and raw coke tail powder with a particle size of less than 6μm; The volatile matter content of raw coke tail powder and coke powder is 8-20%, and the true density is 1.3-1.5 g / cm³. 3 The sulfur content is 0.5%~4%; Raw coke tail powder, polymer a, polymer b, and pore-forming agent are mixed and granulated to obtain coke F1; The thermal decomposition temperature of polymer a is 900~1200℃; Polymer b is a water-soluble polymer; Coke powder and polymer b are mixed and granulated to obtain coke F2. Step 2: Coke F1 and coke F2 are continuously graphitized in a vertical continuous graphitization furnace; The vertical continuous graphitization furnace includes the furnace body; The furnace body consists of two concentric cavities, an outer cavity and an inner cavity, and has a double-cavity coaxial sleeve structure. It is divided into a feeding zone, a preheating zone, a graphitization zone, a cooling zone and a discharging zone from top to bottom in the vertical direction. Both the outer and inner cavities are equipped with material downward channels; the outer cavity has a coke F1 inlet in the feeding area and a GF1 outlet for the graphitized coke F1 product in the unloading area. The inner cavity has a coke F2 inlet in the feeding area and a GF2 outlet in the unloading area for extracting graphitized coke F2 products. The initial stage of continuous graphitization: Coke F1 is filled into the feeding area of ​​the outer cavity, the preheating area of ​​the inner cavity, and the graphitization area of ​​the inner cavity; coke F2 is filled into the feeding area of ​​the inner cavity; after the initial loading, the graphitization area is first heated to the pretreatment temperature T1, and the holding time at temperature T1 is 1~5h; then the temperature is further increased to the graphitization temperature T2 for graphitization; temperature T2 is 2500~3200℃; the holding time at temperature T2 is 2~6h. Continuous graphitization stage: After the initial stage, the graphitized product of coke F1 is collected from the GF1 outlet, and coke F1 is continuously added in the feeding area of ​​the outer cavity. The coke F1 flows through the feeding area, preheating area, graphitization area and cooling area of ​​the outer cavity, and the graphitized product of coke F1 is collected from the GF1 outlet of the unloading area. Furthermore, coke F2 is continuously added in the inner cavity feeding zone. The coke F2 flows through the inner cavity feeding zone, preheating zone, graphitization zone, and cooling zone, and the coke F2 graphitization product is collected from the GF2 outlet in the unloading zone. The temperature of the material in the cooling zone is 80~200℃.

2. The preparation method of the all-coke-based graphite anode material as described in claim 1, characterized in that, Polymer a includes at least one of high-temperature asphalt and high-temperature resin; Polymer b includes at least one of sodium carboxymethyl cellulose, sodium carboxymethyl starch, starch, hydroxypropyl cellulose, polyacrylic acid, sodium polyacrylate, acrylic acid-acrylamide copolymer, and polyvinyl alcohol; Pore-forming agents include at least one of silicon carbide, boron nitride, and nickel chloride; The weight ratio of raw coke tail powder, polymer a, polymer b, and pore-forming agent is 1:0.01~0.05:0.01~0.05:0.001~0.01; The weight ratio of coke powder to polymer b is 1:0.01~0.

05.

3. The method for preparing the all-coke-based graphite anode material as described in claim 1, characterized in that, Temperature T1 is 600~1200℃.

4. The method for preparing the all-coke-based graphite anode material as described in claim 3, characterized in that, The heating rate V1 to temperature T1 is 2~10℃ / min.

5. The method for preparing the all-coke-based graphite anode material as described in claim 3, characterized in that, The heating rate V2 to temperature T2 is 10~50℃ / min.

6. A coke-based graphite anode material prepared by the preparation method according to any one of claims 1 to 5.

7. The application of a coke-based graphite anode material prepared by the preparation method according to any one of claims 1 to 5, characterized in that, It is used to manufacture lithium-ion batteries.

8. A lithium-ion battery, characterized in that, The invention comprises the coke-based graphite anode material prepared by the preparation method according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Method for preparing composite graphite negative electrode material

    CN105990581A

  • Preparation method of low-cost composite particle graphite cathode material

    CN109748274A

  • Method for converting carbon by using petroleum coke to calcine graphite

    CN113353913A

  • Waste graphite-based rate type artificial graphite negative electrode material as well as preparation and application thereof

    CN120247011A